2019
DOI: 10.1002/fsn3.977
|View full text |Cite
|
Sign up to set email alerts
|

Low intakes of dietary fiber and magnesium are associated with insulin resistance and hyperandrogenism in polycystic ovary syndrome: A cohort study

Abstract: Background Women with polycystic ovary syndrome (PCOS) often have insulin resistance (IR) which may be worsened by obesity. The roles of dietary intake and activity are unclear. Our objectives were to determine whether (a) high caloric intake or inactivity explains obesity in PCOS, and (b) dietary composition is associated with PCOS phenotypes. Methods Eighty‐seven women with PCOS and 50 women without PCOS participated in this cohort study at a reproductive medicine cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
2
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 60 publications
2
31
2
7
Order By: Relevance
“…Our findings also corroborate existing evidence that women with PCOS meet recommended macronutrient distribution ranges [13,14,15,18,19,22]. We noted that our participants exhibited marginally low intakes of dietary fiber (24 g/d), and therefore mirrored the previous observations made by our group and Cutler et al (2019) in Canadian women [20,50]. Women with PCOS also had excessive sodium intake.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings also corroborate existing evidence that women with PCOS meet recommended macronutrient distribution ranges [13,14,15,18,19,22]. We noted that our participants exhibited marginally low intakes of dietary fiber (24 g/d), and therefore mirrored the previous observations made by our group and Cutler et al (2019) in Canadian women [20,50]. Women with PCOS also had excessive sodium intake.…”
Section: Discussionsupporting
confidence: 92%
“…The possibility of excessive energy intake in women with PCOS is controversial. Some studies have reported similar energy intake and physical activity between women with and without PCOS [15,18,19,20], while others have identified a positive energy balance in women with PCOS, secondary to excessive caloric intake and sedentary lifestyle behaviors [10,13,21,22]. Improved diet quality has also been observed in women with PCOS, albeit in conjunction with increased energy intake and longer sitting intervals [14].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the result of our research, previous studies demonstrated an inverse association between dietary Mg intake and insulin resistance and a dose-effect relationship [21][22][23][24]. However, there is a lack of relevant research in Asian population and most Asian studies focused on the relationship between dietary Mg and the risk of diabetes, which were inconsistent.…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with the result of our research, previous studies have demonstrated an inverse association and a dose-effect relationship between dietary Mg intake and insulin resistance. [22][23][24][25] However, there is a lack of relevant research in Asian populations, and most Asian studies have focused on the relationship between dietary Mg and the risk of diabetes, showing inconsistent results. Some studies showed that high dietary Mg intake could reduce Notes: Data are expressed as coefficients (95% CI).…”
Section: Discussionmentioning
confidence: 99%